MENINGKATKAN HASIL BELAJAR SISWA MELALUI MODEL PEMBELAJARAN THINK-PAIR-SQUARE (TPS) PADA MATA PELAJARAN IPS DALAM MATERI SUMBER DAYA ALAM KITA KELAS IV SDN 04 BUKIT HARAPAN KECAMATAN KERINCI KANAN KABUPATEN SIAK - Siti Maryam (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2016)
Classroom action research was motivated by the phenomena that show low student learningoutcomes, among which are 1) most of the students can not complete the task and Homework(PR), 2) some students can not answer the post test, 3) Average daily values pupils is low iebelow the minimum completeness criteria (KKM) is 70. Therefore, researchers appliedlearning model Think-Pair-Square (TPS), which aims to improve student learning outcomesIPS. The problems of this study is whether the learning model Think-Pair-Square (TPS) toimprove learning outcomes for Social Sciences in the material type and distribution of naturalresources in the fourth grade SDN 04 Bukit Harapan Kecamatan Kerinci Kanan KabupatenSiak?. The object of this study is the use of learning model Think-Pair-Square (TPS), whilethe subject of this study is all fourth grade students of SDN 04 Bukit Harapan KecamatanKerinci Kanan Kabupaten Siak, the academic year 2015/2016 the number of students as manyas 22 people. This research was conducted in two cycles, each cycle is done in three sessions,To study this class action work well without barriers obstructing the smooth running of thestudy, researchers compiled stages are passed in classroom action research, namely: 1)planning/ preparatory actions 2) Implementation of the action, 3) observation, and 4)reflection. Based on the results of preliminary observations, student learning outcomesobtained in classical completeness percentage is 41%, this figure has not reached the successthat has been established in this study. Then based on the results of tests on the first cycleshowed that the level of student learning outcomes achieve classical completeness percentageis 64%, this figure has not reached the success that has been established in this study is 75%,therefore the next cycle continued. While on the second cycle increased achieve learningoutcomes of students gaining the percentage of classical completeness is 100%, meaning thatthis figure has exceeded the success rate has been established in this study and theachievement of 100% value in the classical completeness, this research was successful.